Тайна: [роман] / Олег Рой - Рой Олег (Капризы судьбы, 2014)
Экземпляры: Ф-2 (20210322) / Инвентарный номер: 96038 / Цена: / Сис.шифр: 84 (2=411.2)6-4 / Авт.знак: Р 65 / ГРНТИ: 17.82 / ББК: 84 (2=411.2)6-4